Preparation of three-component covalent organic framework and application of three-component covalent organic framework in photocatalytic water splitting

By introducing the third component Pt@TpTzDb-COF into the photocatalyst, the problem of electron holes easy recombination of the two-component COFs photocatalyst is solved, significantly improving the efficiency of photocatalytic decomposition of water, and achieving higher hydrogen and oxygen production efficiency.

CN119869613APending Publication Date: 2025-04-25HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510047417.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The ordinary two-component COFs photocatalyst has a rapid recombination of photogenerated electrons and holes, resulting in a low separation efficiency of photogenerated carriers, limiting its efficiency in the photocatalytic full water dissolution process.

Method used

Using solvothermal method, benzo[1,2-d:4,5-d’]bis(thiazole)-2,6-diamine and Tp as raw materials, Pt NPs were added in situ, and a three-component Pt@TpTzDb-COF composite material was successfully synthesized.

Benefits of technology

The photocatalytic water decomposition performance is effectively improved, with hydrogen production efficiency of 64μmol·h-1·g-1 and oxygen production efficiency of 32μmol·h-1·g-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005238904880000011
    Figure HDA0005238904880000011
  • Figure HDA0005238904880000012
    Figure HDA0005238904880000012
  • Figure HDA0005238904880000021
    Figure HDA0005238904880000021
Patent Text Reader

Abstract

The invention relates to preparation of a three-component Pt-coated TpTzDb-COF composite material and application of the three-component Pt-coated TpTzDb-COF composite material to photocatalytic water decomposition. The invention provides a novel three-component COF composite material, and aims to solve the problems that the light utilization rate is low and electron holes are easy to compound when the conventional two-component COF is used for photocatalytic decomposition of water. The method comprises the following steps: 1, preparing Pt NPs; (2) preparation of Pt (at) TpTz-COF; 3, preparing the Pt (at) TpDb-COF; and 4, preparing the Pt (at) TpTzDb-COF. The preparation process is simple and effective, the reagent consumption is low, and the performance is high; the photocatalyst provided by the invention can effectively solve the problem of low photocatalytic water decomposition efficiency. The composite material is applied to the field of photocatalytic water decomposition, experiments show that the composite material has excellent photocatalytic water decomposition performance, the water decomposition hydrogen production rate under visible light irradiation can reach 64 [mu] mol.h <-1 >. G <-1 >, and the oxygen production efficiency is 32 [mu] mol.h <-1 >. G <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a Pt@TpTzDb-COF composite material and its application in photocatalytic water decomposition. Background Art

[0002] Solar photocatalytic water splitting to produce hydrogen is an effective method for converting clean renewable energy solar energy into green hydrogen energy, and has attracted widespread attention from researchers. Hydrogen energy can be used as an energy carrier to help reduce dependence on traditional fossil fuels (such as oil, natural gas and coal). With the growth of global energy demand and the gradual reduction of fossil fuel resources, it is crucial to find alternative energy sources. The development of hydrogen energy helps to diversify energy supply and reduce the risk of energy crisis caused by the interruption of single energy supply. In the past few decades, people have made great efforts in the design and synthesis of photocatalysts. Inorganic semiconductors such as titanium oxide (TiO2), cadmium sulfide (CdS) and zinc oxide (ZnO) have a clear crystal structure and have been proven to be efficient and sustainable materials for solar-driven hydrogen production. Photocatalytic water splitting technology uses solar energy as the driving force to realize the conversion and storage of solar energy into chemical energy by decomposing water molecules into hydrogen and oxygen. This method can not only solve the current problem of tight energy supply, but also alleviate the environmental degradation caused by the excessive use of fossil energy. However, ordinary two-component COFs photocatalysts may have a rapid recombination of photogenerated electrons and holes, resulting in a low separation efficiency of photogenerated carriers, thus limiting its efficiency in the photocatalytic water splitting process. Therefore, constructing three-component COFs, making more efficient use of visible light, and improving the electron-hole separation efficiency for better water splitting has become a new research hotspot.

[0003] Covalent organic frameworks are organic polymer materials with extended periodic arrangement structures formed by covalent connection between organic ligand units, which can have one-dimensional, two-dimensional and three-dimensional spatial configurations. In recent years, covalent organic frameworks have rapidly developed into emerging photocatalyst materials due to their unique advantages. Covalent organic frameworks have excellent porous properties, large specific surface area, rich active surface for catalytic reactions, and pore structure is conducive to the enrichment of reactants; its constituent units and connection methods can be designed and adjusted, so the final structure is rich and diverse, which provides a huge material platform for photocatalysis, and atomic-level regulation is conducive to the study of photocatalytic mechanisms. At present, in the field of photocatalytic water splitting, research mainly focuses on constructing new covalent organic framework photocatalysts, realizing efficient charge separation and transfer inside the material, and constructing efficient surface catalytic active sites. Therefore, it is very meaningful and challenging to design and construct efficient composite photocatalysts with energy band matching, interface matching and built-in electric field to achieve efficient transportation of photogenerated electrons and holes in the field of photocatalytic water splitting. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the electron holes of the ordinary two-component COFs photocatalyst are easy to recombine and the water decomposition efficiency is not high, and to provide a preparation method of a three-component Pt@TpTzDb-COF composite material and its application in photocatalytic water decomposition.

[0005] The preparation method of a three-component Pt@TpTzDb-COF composite material of the present invention is completed by the following steps: 1. Preparation of Pt@TpTz-COF: Tp and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine, 2mL of a mixed solution of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) were sequentially loaded into a Schronck glass tube. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2mL of 6.0M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum-sealed state. The dark red precipitate formed was collected by centrifugation or filtration, washed with DMF and acetone 5-6 times in sequence, and the collected powder was solvent exchanged with acetone 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpTz-COF with a yield of about 85%. 2. Preparation of Pt@TpDb-COF: Tp and 2,5-diaminobenzonitrile, 2 mL of a mixed solution of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) were sequentially loaded into a Schronck glass tube. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2 mL of 6.0 M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum sealed state. The dark red precipitate formed was collected by centrifugation or filtration, washed with DMF and acetone 5-6 times in turn, and the collected powder was solvent exchanged with acetone 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpDb-COF with a yield of about 83%. 3. Preparation of Pt@TpTzDb-COF: Tp and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine and 2,5-diaminobenzonitrile were sequentially placed in a Schronck glass tube, and a mixed solution of 2 mL of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) was added. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2 mL of 6.0 M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum sealed state. The formed dark red precipitate was collected by centrifugation or filtration, washed with DMF and acetone for 5-6 times, the collected powder was solvent exchanged with acetone for 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpTzDb-COF with a yield of about 80%. The concentration of the n-butanol solution containing Pt NPs used in the above steps was 2.96 mg / ml; The mass ratio of Pt NPs to COFs in the above steps was 0.03:1; In the above steps, the molar ratio of Tp to benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine and 2,5-diaminobenzonitrile is 4:3:3; In the step, the volume ratio of o-dichlorobenzene, n-butanol and acetic acid is 0.5:1.5:0.2; The mixture was sealed and heated at 120°C for 72 h. Application of the above-mentioned Pt@TpTzDb-COF composite material in photocatalytic water decomposition.

[0006] Beneficial effects of the present invention: The present invention adopts a solvothermal method, uses benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine and Tp as raw materials, and successfully synthesizes Pt@TpTz-COF by in-situ addition of Pt NPs. However, the efficiency of water decomposition under visible light is relatively low, which is 18 μmol·h -1 ·g -1 Therefore, the invention synthesizes three-component COF by combining Tp, benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine and 2,5-diaminobenzonitrile to synthesize Pt@TpTzDb-COF composite material, which effectively improves the photocatalytic water decomposition performance and has a hydrogen production efficiency of 64μmol·h -1 ·g -1 , oxygen production efficiency is 32 μmol·h -1 ·g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1X-ray powder diffraction pattern of Pt@TpTzDb-COF material; Figure 2 This is the infrared spectrum of Pt@TpTzDb-COF material; Figure 3 This is the photocatalytic water decomposition performance diagram of Pt@TpTzDb-COF material. DETAILED DESCRIPTION

[0008] The present invention is further described below with reference to examples. These examples are only used to illustrate the method of the present invention and have no limitation on the scope of application of the present invention.

[0009] Example 1: The preparation of a Pt@TpTzDb-COF material of this embodiment is completed according to the following steps: 1. Preparation of Pt nanoparticles: Add chloroplatinic acid solution, polyvinyl pyrrolidone (PVP), ethylene glycol solution containing sodium hydroxide and ethylene glycol into a three-necked flask, stir and heat under vacuum, and keep at 180°C for 3 minutes. Cool to room temperature, centrifuge the resulting solution with acetone, wash it several times with n-hexane, let it stand for one minute until the n-hexane evaporates, and add 2 ml of n-butanol to disperse the Pt nanoparticles. The concentration of the chloroplatinic acid solution in step 1 is 7.4 mg / ml; The concentration of the ethylene glycol solution containing sodium hydroxide in step 1 is 0.2 mol·L -1 ; The volume ratio of the chloroplatinic acid solution, the ethylene glycol solution containing sodium hydroxide and ethylene glycol in step 1 is 0.5:1:5; The concentration of the n-butanol solution containing Pt NPs in step 1 is 2.96 mg / ml. 2. Preparation of Pt@TpTz-COF: Tp and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine, 2mL of a mixed solution of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) were sequentially loaded into a Schronck glass tube. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2mL of 6.0M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum sealed state. The dark red precipitate formed was collected by centrifugation or filtration, washed with DMF and acetone 5-6 times in sequence, and the collected powder was solvent exchanged with acetone 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpTz-COF with a yield of about 85%. The concentration of the n-butanol solution containing Pt NPs used in step 2 is 2.96 mg / ml; The mass ratio of Pt NPs to TpDb-COF in step 2 is 0.03:1; The molar ratio of Tp to benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine in step 2 is 2:3; The volume ratio of o-dichlorobenzene, n-butanol and acetic acid in step 2 is 0.5:1.5:0.2; After sealing as described in step 2, the mixture was heated at 120°C for 72 h. 3. Preparation of Pt@TpDb-COF: Tp and 2,5-diaminobenzonitrile, 2mL of a mixed solution of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) were sequentially loaded into a Schronck glass tube. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2mL of 6.0M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum sealed state. The dark red precipitate formed was collected by centrifugation or filtration, washed with DMF and acetone 5-6 times in turn, and the collected powder was solvent exchanged with acetone 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpDb-COF with a yield of about 83%. The concentration of the n-butanol solution containing Pt NPs used in step 3 is 2.96 mg / ml; The mass ratio of Pt NPs to TpDb-COF in step 3 is 0.03:1; The molar ratio of Tp to 2,5-diaminobenzonitrile in step 3 is 2:3; The volume ratio of o-dichlorobenzene, n-butanol and acetic acid in step 3 is 0.5:1.5:0.2; After sealing as described in step 3, heat at 120°C for 72h. 4. Preparation of Pt@TpTzDb-COF: Tp and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine and 2,5-diaminobenzonitrile were sequentially placed in a Schronck glass tube, and a mixed solution of 2 mL of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) was added. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2 mL of 6.0 M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum sealed state. The formed dark red precipitate was collected by centrifugation or filtration, washed with DMF and acetone for 5-6 times, the collected powder was solvent exchanged with acetone for 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpTzDb-COF with a yield of about 80%. The concentration of the n-butanol solution containing Pt NPs used in step 4 is 2.96 mg / ml; The mass ratio of Pt NPs to TpTzDb-COF in step 4 is 0.03:1; The molar ratio of Tp to benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine and 2,5-diaminobenzonitrile in step 4 is 4:3:3; The volume ratio of o-dichlorobenzene, n-butanol and acetic acid in step 4 is 0.5:1.5:0.2; After sealing as described in step 4, heat at 120°C for 72h.

[0010] To verify the beneficial effects of the present invention, the following test was conducted: To investigate the photocatalytic water decomposition effect of Pt@TpTzDb-COF material, its visible light photocatalytic water decomposition performance was tested according to the following method. The test process is as follows: Pt@TpTzDb-COF (10 mg) was used as the photocatalyst and distilled water (50 ml) was used as the reaction liquid. Under visible light conditions, the efficiency of hydrogen production by photocatalytic water decomposition of Pt@TpTz-COF alone was low, only 18 μmol·h -1 ·g -1 , oxygen production is only 9 μmol·h -1 ·g -1 The Pt@TpTzDb-COF composite material exhibited excellent photocatalytic water splitting performance, with a photocatalytic water splitting hydrogen production efficiency of 64 μmol·h -1 ·g -1 , oxygen production efficiency is 32μmol·h -1 ·g -1 .

Claims

1. Preparation of Pt@TpTz-COF, Pt@TpDb-COF and Pt@TpTzDb-COF composite materials, characterized in that The method proceeds as follows:

1. Preparation of Pt@TpTz-COF: Tp and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine, 2mL of a mixed solution of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) were sequentially loaded into a Schronck glass tube. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2mL of 6.0M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum-sealed state. The dark red precipitate formed was collected by centrifugation or filtration, washed with DMF and acetone 5-6 times in sequence, and the collected powder was solvent exchanged with acetone 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpTz-COF with a yield of about 85%.

2. Preparation of Pt@TpDb-COF: Tp and 2,5-diaminobenzonitrile, 2 mL of a mixed solution of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) were sequentially loaded into a Schronck glass tube. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2 mL of 6.0 M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum sealed state. The dark red precipitate formed was collected by centrifugation or filtration, washed with DMF and acetone 5-6 times in turn, and the collected powder was solvent exchanged with acetone 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpDb-COF with a yield of about 83%.

3. Preparation of Pt@TpTzDb-COF: Tp and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine and 2,5-diaminobenzonitrile, 2mL of a mixed solution of o-dichlorobenzene and n-butanol (Pt-n-butanol ratio = 0, 11.4, 34.7, 58, V / V%) were sequentially placed in a Schronck glass tube. The mixture was ultrasonically treated for 10-15 minutes to obtain a uniform dispersion, and then 0.2mL of 6.0M acetic acid aqueous solution was added. The Schronck tube was quickly frozen in 77K (liquid nitrogen bath) and degassed through three freeze-thaw cycles, and finally the tube was heated at 120°C for 72 hours in a vacuum sealed state. The formed dark red precipitate was collected by centrifugation or filtration, washed with DMF and acetone for 5-6 times, the collected powder was solvent exchanged with acetone for 3 times, and finally vacuum dried at 60°C for 24 hours to obtain Pt-X% / TpTzDb-COF with a yield of about 80%.

2. The preparation of a Pt@TpTz-COF composite material according to claim 1, characterized in that In step 1, the molar ratio of Tp to benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 2:

3.

3. The preparation of a Pt@TpDb-COF composite material according to claim 1, characterized in that The molar ratio of Tp to 2,5-diaminobenzonitrile in step 2 is 2:

3.

4. The preparation of a Pt@TpTzDb-COF composite material according to claim 1, characterized in that In step 3, the molar ratio of Tp to benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine and 2,5-diaminobenzonitrile is 4:3:3.